UPAYA PENINGKATAN KEMAMPUAN GURU DALAM PENYELENGGARAAN PENDIDIKAN INKLUSIF DI LEMBAGA PENDIDIKAN ANAK USIA DINI (PAUD) - Rahmi, Fathiya Nur; Wijayanti, Sri (Jurnal Abdi Masyarakat Indonesia (JAMIN), 2024)
Inclusive education is crucial to implement, particularly in early childhood education. It can help students with different conditions. However, in the Cianjur Regency area, two early childhood education institutions faced obstacles in identifying student's initial conditions, developing learning activities, and involving parents to support inclusive learning. To address these challenges, this community service project was held to improve teachers' abilities to provide inclusive education consisting of General, Basic, and Specific Abilities. The project adopted the GROW Coaching Model approach, which includes Goal, Reality, Options, and Will. It began with a psychological development and academic maturity test for students from both schools, followed by counseling with parents and discussions among teachers and presenters on students' conditions. The project results helped implement General and Basic Abilities, such as accepting diversity and identifying student conditions. As a result, teachers can now apply Special Abilities or modify inclusive learning processes.